Design and Construction of Automatic pH and Water Level Control in Tilapia Fish Farming Ponds - Patwan Saputra; Christio Revano Mege; Ferizandi Qauzar Gani (Universitas Mercu Buana, 2026)
This study presents the design and implementation of an automatic control system for regulating pH and water level in tilapia (Oreochromis niloticus) aquaculture ponds. The system integrates a pH sensor and an ultrasonic sensor (HC-SR04) with an ESP32 microcontroller to enable real-time monitoring and automated control through solenoid valves. Sensor calibration was performed using standard buffer solutions (pH 4.00, 7.00, and 10.00) based on potentiometric principles derived from the Nernst equation, resulting in high linearity and reliable measurement accuracy. Experimental evaluation demonstrates that the proposed system is capable of maintaining water quality parameters within the optimal range required for tilapia cultivation. The pH control system achieved its best performance with a settling time of 1950 s and a steady-state error of 0.93%, indicating stable and accurate regulation. For water level control, the system exhibited a settling time of 7570 s during the filling process and 2965 s during the draining process, both with negligible steady-state error, confirming high control precision. Although the system shows relatively slow dynamic response due to hydraulic and actuator limitations, the gradual adjustment is advantageous in aquaculture applications, where sudden environmental changes can negatively affect fish health. Overall, the developed system provides a low-cost, reliable, and practical solution for improving aquaculture management through automation. Future work should focus on implementing adaptive control algorithms, enhancing sensor performance, and integrating IoT-based monitoring platforms to support scalability and remote operation.